Fabrication and electrochemical properties of a graphene-enhanced hierarchical porous network of Fe3O4/carbon nanobelts. (10th September 2017) - Yu, Xing; Wang, Mengyi; Gagnoud, Annie; Fautrelle, Yves; Moreau, Rene; Li, Xi
Highlights: A graphene-enhanced hierarchical porous network of Fe3 O4 /carbon nanobelts (MGP6S ) was fabricated. A novel, facile and scalable process of simultaneous activation and templating is developed. The graphene sheets behave as a chemical activator to promote the growth of MGP6S . An excellent supercapacitive performance was obtained using MGP6S as the electrode. Abstract: A novel, facile and scalable process of simultaneous activation and templating is developed for in situ synthesis of graphene-enhanced 3D hierarchical porous carbon nanobelt networks uniformly anchored with polycrystalline Fe3 O4 nanoparticles (5–45 nm) (Fe3 O4 –rGO/poly(vinyl alcohol) (PVA)-derived carbon) as a high-performance supercapacitor electrode. During the synthesis, 3D self-assembled NaCl particles are adopted as a structural template to direct the growth of 3D carbon nanobelt networks with interconnected macropores, KOH is used as an activating reagent to generate porous nanobelts with masses of micro-, meso- and macropores, and graphene sheets behave as a chemical activator to promote the growth of hierarchical porous thin nanobelts. The resulting Fe3 O4 –rGO/PVA-derived carbon electrode leads to a combination of the redox pseudo-capacitance of Fe3 O4 and the electric double-layer capacitance of the carbon species with a remarkably high capacitivity (538.8 F g −1 at 5 A g −1 ) and outstanding cycle performance (∼590 F g −1 after 5000 cycles at 5 A g −1 ). This work offers a new strategy for preparation of 3D hierarchical porous carbon networks for future applications.